2015
DOI: 10.1016/j.apm.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the arterial wall mechanics using a novel high-order viscoelastic fractional element

Abstract: a b s t r a c tThe fractional viscoelastic models (FVMs) have provided promising results for modeling the behavior of complex materials such as polymers and living tissues. These viscoelastic models are composed by springs, dashpots and the fractional element called spring-pot. In this paper we prove that the accuracy of these models can be improved through the use of a modified version of the spring-pot element, called high-order spring-pot (HOSP).We describe and implement a numerical method for characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Only the model with two spring-pots correctly followed the activation state with the best performance. Stress relaxation of human arteries was then described with this methodology in [ 39 ] and its numerical approach was introduced in [ 40 ].…”
Section: Applied Nonlinear Dynamicsmentioning
confidence: 99%
“…Only the model with two spring-pots correctly followed the activation state with the best performance. Stress relaxation of human arteries was then described with this methodology in [ 39 ] and its numerical approach was introduced in [ 40 ].…”
Section: Applied Nonlinear Dynamicsmentioning
confidence: 99%
“…Regarding cardiovascular mod-eling, the power-law behavior has been demonstrated in describing human soft tissues' visco-elasticity and characterizing the elastic vascular arteries. The in-vivo and in-vitro experimental studies have pointed out that fractional-order calculus-based approaches are more decent to represent the hemodynamic precisely; the viscoelasticity properties of soft collagenous tissues in the vascular bed; the aortic blood rate [22]- [24]; red blood cell (RBC) membrane mechanical properties [25] and the heart valve cusp [23], [26]- [28]. In addition, recently, we developed novel fractional-order arterial Windkessel representations, [29]- [31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, the power-law behavior has been proved in the viscoelastic characterization of an elastic aorta. The in-vivo and in-vitro data analysis showed that the FD tools make it more convenient to accurately model and describe the arterial wall viscoelastic dynamic response (Craiem and Armentano 2007, Craiem and Magin 2010, Perdikaris and Karniadakis 2014, Zerpa et al 2015. Besides, a recent study by the authors , 2018, used fractional-order derivative tools with the wellknown arterial Windkessel paradigm, by replacing the ideal capacitor (which accounts for the total arterial compliance) with a fractional-order capacitor.…”
Section: Introductionmentioning
confidence: 99%